Efforts to Improve Student Thematic Learning Outcomes Through the Pair Check Model in class 1 of SDN 3 Gombang Cawas Klaten - Lestari, Nani (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
This research aims to obtain information about efforts to improve student Thematic learning outcomes through the Pair Check method in Class I SDN 3 Gombang, Cawas, Klaten Regency. This type of research is Classroom Action Research (PTK). The subjects of this research were Class I students with a total of 16 students. The place of this research was carried out at SDN 3 Gombang. The PTK implementation time is in the second semester of the 2018/2019 academic year. This research was carried out in 2 cycles with planning, implementation, observation and reflection procedures. Data was collected using test results and observation sheets. Data was analyzed percentage, qualitative and quantitative. This research found that there was an increase in student learning outcomes by using the Pair Check learning model.